Finland Through Australian Eyes - Bonetti, Ruth (Migration-Muuttoliike, 2015)
Wilhelm Anders Back (29.7.1886–2.4.1974) immigrated to Australia on 26 November 1902 – a 16-year old eager to take on the world. He and his brother Karl Johan Back (20.10.1877–20.6.1962) settled in the Byron Bay-Mullumbimby area of New South Wales. They often wrote home to urge their family to sell the farm and emigrate to the ‘Promised Land.’ Civil War intervened and the elderly parents baulked. Wilhelm travelled in 1924 to Finland – via the world at large – to encourage and persuade. That yearlong Grand Tour culminated in a Finnish summer. He sponsored a wave of migration from Ostrobothnia – but his own family was not amongst this.